Reconceptualizing Online Purchase Decision: The Strategic Role of Economic Benefit, Convenience, and Transaction Flexibility in Indonesia - Mohamad Sodikin; Amanda Dwi Lestari; Erminia Nacwa Sava; Indah Kusuma Saputri; Caesilia Sagita Angel; Susmiyati; Febi Lusia Lim; Orinda Jayanti Pungkasari; Lenita Ganis Septiani; Atthariq Roiyan Zulmi; Lungguh Herwanto (E-logis : Jurnal Ekonomi Logistik, 2026)
Despite extensive research on online consumer behavior, existing studies largely emphasize purchase intention and isolate determinants such as price, trust, or perceived usefulness. Limited attention has been paid to how consumers integrate multiple evaluative dimensions in forming actual online purchase decisions, particularly in emerging digital markets. Addressing this gap, this study reconceptualizes online purchase decision as a multidimensional evaluative process by examining Indonesian's consumers lived experiences in e-commerce transactions. Using an exploratory qualitative design, data were collected from 30 active online shoppers through semi-structured interviews and analyzed via reflexive thematic analysis. The results identify three interrelated yet distinct dimensions shaping purchase decisions: Perceived Economic Benefit, Perceived Convenience, and Transaction & Access Flexibility. While economic benefit reflects utilitarian value optimization and cost efficiency, and convenience captures effort and time reduction, transaction and access flexibility emerges as a structurally distinct determinant representing perceived control through adaptive payment options, temporal accessibility, and mobile-based access. This study advances the literature by positioning transaction flexibility as an independent construct rather than a subdimension of convenience or trust. Theoretically, the findings integrate consumer value, technology acceptance, and transaction cost perspectives into a unified framework explaining actual purchase behavior. Managerially, the study highlights the strategic importance of designing flexible transaction systems alongside competitive pricing and seamless user experience in emerging e-commerce ecosystems.